Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada Rumah Sakit Prikasih Jakarta Selatan - Lestari, Putri Indah Mei; Azwina, Diana (Prodi Manajemen, Fakultas Ekonomi, Universitas Pamulang, 2024)
The aim of this research is to determine the influence of the work environment and work discipline on employee performance at Prikasih Hospital, South Jakarta, both partially and simultaneously. The method used in this research is quantitative. The sampling technique used the slovin formula sampling and the sample in this study consisted of 80 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. Partials are written too.The results of the hypothesis test for Work Environment (X1) and Work Discipline (X2) partially have tcount values ​​of 9.733 (X1) and 10.296 (X2), meaning that all tcount>ttable values. For the simultaneous effect of the Employee Performance variable (Y) the value of Fcount > Ftable is 73.525 > 3.115. The significance level is 0.1. So it can be concluded that the Work Environment and Work Discipline partially or simultaneously have a significant effect on Employee Performance. With the linear regression equation Y = 9.389 + 0.306 X1 + 0.460 The coefficient of determination value of 0.656 explains that the Work Environment and Work Discipline have an effect on Employee Performance of 0.656